2013
DOI: 10.1016/j.dcn.2012.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Ventral striatum activation to prosocial rewards predicts longitudinal declines in adolescent risk taking

Abstract: Adolescence is a period of intensified emotions and an increase in motivated behaviors and passions. Evidence from developmental neuroscience suggests that this heightened emotionality occurs, in part, due to a peak in functional reactivity to rewarding stimuli, which renders adolescents more oriented towards reward-seeking behaviors. Most prior work has focused on how reward sensitivity may create vulnerabilities, leading to increases in risk taking. Here, we test whether heightened reward sensitivity may pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
96
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(104 citation statements)
references
References 45 publications
6
96
1
1
Order By: Relevance
“…In another fMRI study, Telzer et al [25] used the same 'you vs. family' decision-making task as well as the Balloon Analogue Risk Task to check if reward-related neural activity can predict the presence of peer observers, and even more when peers provide prosocial feedback. Contrary to the work of Telzer et al [8,23,25] and Braams et al [26,27], the fMRI data showed that activity of the reward system does not increase during donation choices or when receiving peer feedback. There was, however, an increase in the activity of the social brain network (medial prefrontal cortex, temporoparietal junction, and superior temporal sulcus) in such cases.…”
Section: Reward Sensitivity and Prosocial Behaviourcontrasting
confidence: 99%
See 3 more Smart Citations
“…In another fMRI study, Telzer et al [25] used the same 'you vs. family' decision-making task as well as the Balloon Analogue Risk Task to check if reward-related neural activity can predict the presence of peer observers, and even more when peers provide prosocial feedback. Contrary to the work of Telzer et al [8,23,25] and Braams et al [26,27], the fMRI data showed that activity of the reward system does not increase during donation choices or when receiving peer feedback. There was, however, an increase in the activity of the social brain network (medial prefrontal cortex, temporoparietal junction, and superior temporal sulcus) in such cases.…”
Section: Reward Sensitivity and Prosocial Behaviourcontrasting
confidence: 99%
“…Findings such as those of Telzer et al [8,23,25] and Braams et al [26,27] highlight the crucial role of the reward system in risky or prosocial decisions made by adolescents in various social situations. These findings can be interpreted as follows: due to heightened sensitivity to incentives, adolescents may be particularly prone to choosing actions that are rewarded in the current social context.…”
Section: Purposementioning
confidence: 96%
See 2 more Smart Citations
“…While increased VS activation during adolescence has traditionally been associated with increased sensation seeking and risk-taking, some new research suggests that in the context of meaningful prosocial behavior, it may also be associated with declines in risk-taking (Telzer, Fuligni, Lieberman, & Galván, 2012). The limited capacity of adolescents to predict the emotional pleasure of rewards coupled with an enhanced capacity to experience rewards may help explain their risk-taking and sensation seeking behavior (Crone & Dahl, 2012).…”
Section: Social-emotional Developmentmentioning
confidence: 99%